ROLE OF CORE ELEMENTS OF ORGANIZATIONS IN CONDUCTING DIGITAL TRANSFORMATION IN FASHION SMEs (Case Study of Yogyakarta and Klaten Fashion SMEs) - Muhammad Adib Z (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The speed of the development of information and technology in the current 4.0 Industrial Revolution however cannot be dammed again coupled with the existence of the Covid-19 outbreak. This has an effect on changes in the patterns of consumer behavior and their lifestyle, especially in shopping. So the company is required radically to change their model business in creating and adjusting values. Many companies have adopted a digital transformation strategy to change the way they create and adjust value. Therefore, the formulation of digital strategies must identify the business elements of the company model that must be modified in accordance with the new strategy, along with the scope of the digital transformation. This study examined how the role of the organization's core elements in transforming in the Fesyen SMEs in Yogyakarta and Klaten. The aim is to analyze the core elements of the organization used in carrying out digital transformations to keep the company's competitive advantage, using a qualitative approach with the method of case study, using small and medium enterprises in fashion, such as leather bags, batik, sports jerseys, and typical Muslim clothes Boutique as a research object. The data collection techniques by means of interviews (in depth, structured and open), observation and so on. And data analysis used is descriptive analysis. The results showed that the role of the core elements of the organization had an effect on carrying out digital transformation in the 4 small and medium businesses in Yogyakarta and Klaten. Keywords: Digital Transformation, Core Organizational Elements, Implementation of Digital Transformation